2011
DOI: 10.1007/s10543-011-0335-3
|View full text |Cite
|
Sign up to set email alerts
|

A mass-conservative control volume-finite element method for solving Richards’ equation in heterogeneous porous media

Abstract: We present a mass-conservative vertex-centred finite volume method for efficiently solving the mixed form of Richards' equation in heterogeneous porous media. The spatial discretisation is particularly well-suited to heterogeneous media because it produces consistent flux approximations at quadrature points where material properties are continuous. Combined with the method of lines, the spatial discretisation gives a set of differential algebraic equations amenable to solution using higher-order implicit solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Cumming et al . demonstrated that a CVFEM‐based discretisation could be used to solve the Richards equation (coupled mass conservation and Darcy equations) in heterogeneous porous media with relatively small computational overhead, compared with traditional, coupled velocity pressure‐based formulations. Mass balance was enforced as described by Kirkland et al .…”
Section: Introductionmentioning
confidence: 99%
“…Cumming et al . demonstrated that a CVFEM‐based discretisation could be used to solve the Richards equation (coupled mass conservation and Darcy equations) in heterogeneous porous media with relatively small computational overhead, compared with traditional, coupled velocity pressure‐based formulations. Mass balance was enforced as described by Kirkland et al .…”
Section: Introductionmentioning
confidence: 99%
“…We propose implicit and semi-implicit time stepping discretizations for each of the formulations (3.4), (3.6) and (3.9). Few second order accurate time-stepping schemes were proposed for Richards equation based on the Crank-Nicolson method [19,79,80] and BDF methods [7,26] in their fully implicit form requering Newton or Picard iterations. The Crank-Nicolson method is A-stable but lacks L-stability, and may lead to non-monotone solutions for larger time steps.…”
Section: Temporal Discretizationmentioning
confidence: 99%
“…Space-time finite element methods have been previously used for parabolic equations (see for example [20]) and for reaction-diffusion system (see for example [15]). A recent work on application of control volume finite element in combination with method of lines for solving Richards Equation is recorded in [10]. To the best of the author's knowledge, there has not been any attempt to apply space-time finite element methods technique to Richards Equation.…”
mentioning
confidence: 99%